Ultrasound Assessment of Diaphragm As A Predictor Tool Of Successful Extubation In Mechanically Ventilated Patients - Suang, Kuang Ting (2021)
Background Weaning failure is defined as failure to pass a spontaneous breathing trial or the need for re-intubation within 48 hours following extubation. An estimated 20% of all mechanically ventilated patients will encounter a failed extubation scenario. The pathophysiology of weaning failure is multifactorial but a recent factor of interest described in current literature is that of diaphragm dysfunction. The purpose of this study is to determine the role of ultrasound assessment of diaphragm as a predictor tool of successful extubation in mechanically ventilated patients Methods This study was carried out in Hospital Queen Elizabeth, Sabah and Hospital Universiti Sains Malaysia, Kelantan. Seventy-five mechanically ventilated patients who were planned for extubation and met the inclusion criteria were enrolled into the study. Written consent was obtained from the next of kin. Bedside diaphragmatic ultrasound was carried out prior to extubation to assess diaphragm excursion and diaphragm thickness fraction. The diaphragm ultrasound was performed by the clinician who had no role in the management of the patients. Extubation was based on intensivist’s or anaesthetist’s decision who were blinded of the ultrasound results. The patients were followed up for 48 hours post extubation. Results There was a statistically significant difference in both the mean diaphragm excursion and the mean diaphragm thickness fraction between the successful extubation group and the failed extubation group. When the diaphragm thickness fraction increased by 1 %, the chance of successful extubation increased by 1.29 times. Conclusion Ultrasound assessment of diaphragm thickening fraction can be used as a predictor tool of successful extubation in mechanically ventilated patients.